Class of Meromorphic Univalent Functions with Fixed Second Positive Coefficients Defined by q-Difference Operator: Class of Meromorphic Univalent Functions with Fixed Second Positive Coefficients - Saleh, Zienab M.; Mostafa, Adela O. (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2022)
In this paper using a q-difference operator, a class of meromorphic univalent functions with fixed second positive coefficients is defined. Coefficient estimates, some distortion theorems and other properties for this class are obtained. Various results obtained are sharp.